Disillusionment and Suicidality: When a Developmental Necessity Becomes a Clinical Challenge. (April 2018) - Tillman, Jane G.
Both illusion and disillusion play an important role in development, fostering processes of going-on-being and separation (Winnicott 1960). The capacity to bear disillusionment is both a developmental necessity and an ongoing challenge. Disillusionment penetrates the sphere of illusion and invites the individual into an expanded encounter with shared realities. But when disillusionment becomes chronic and pervasive or is accompanied by severe psychic pain, then suicide is felt by some to be an urgent option for refusing or escaping this pain. Contextualized within a review of psychoanalytic developmental theories of disillusion, vignettes from a research study of participants who have survived a near lethal suicide attempt illuminate the phenomenon of suicide as an illusory solution to what feels like unbearable disillusionment.